E-Cigarettes as a Growing Threat for Children and Adolescents: Position Statement From the European Academy of Paediatrics - Bush, Andrew; Lintowska, Agnieszka; Mazur, Artur; Hadjipanayis, Adamos; Grossman, Zacchi; del Torso, Stefano; Michaud, Pierre-André; Doan, Svitlana; Romankevych, Ivanna; Slaats, Monique; Utkus, Algirdas; Dembiński, Łukasz; et al. (Frontiers in Pediatrics, 2021)
As the tobacco epidemic has waned, it has been followed by the advent of electronic nicotine delivery devices (ENDS) primarily manufactured by the tobacco industry to try to recruit replacements for deceased smokers. This document sets out the ten recommendations of the EAP with regard to e-cigarettes and children and young people (CYP). The EAP notes that nicotine is itself a drug of addiction, with toxicity to the foetus, child and adult, and were ENDS only to contain nicotine, their use to create a new generation of youth with nicotine addiction would be rigorously opposed. However, e-cigarettes include numerous unregulated chemicals, including known carcinogens, whose long term and many acute toxicities are unknown. The EAP asserts that there is incontrovertible evidence that the acute toxicity of e-cigarettes is greater than that of “traditional” tobacco smoking, and a variety of acute pulmonary toxicities, including acute lung injuries, have been recorded due to e-cigarettes usage. The chronic toxicity of e-cigarettes is unknown, but given the greater acute toxicity compared to tobacco, the EAP cannot assume that e-cigarettes are safer in the long term. The high uptake of e-cigarettes by CYP, including under-age children, is partly fuelled by deceitful marketing and internet exposure, which is also unregulated. Although proposed as aids to smoking cessation, there is no compelling evidence that e-cigarettes add anything to standard smoking cessation strategies. In summary, the EAP regards these devices and liquids as very dangerous, and ineluctably opposed to their use, and their direct or indirect marketing.